PERAN PENGELOLA KELEMBAGAAN USAHA MIKRO KECIL MENENGAH SAAT PANDEMI COVID-19 STUDI DINAS PERINDUSTRIAN PERDAGANGAN KOPERASI DAN UKM KABUPATEN MUKOMUKO - Nine Septya Anggraini (Universitas Muhammadiyah Bengkulu, 2021)
Abstract: This study aimed to determine the role of institutional manager of micro, small and medium business during the Covid-19 Pandemic, study on the Departement of Industry Trade, Cooperatives and UKM, Mukomuko district. This research used a qualitative approach with data collection techniques by conducting observation, interview and documentation. The data was analyzed by combining it into categories, breaking down into units to choose which ones are important to answer the existing problems. The results of the research show that the the role of institutional manager of micro, small and medium business during the Covid-19 Pandemic on the Departement of Industry Trade, Cooperatives and UMKM, Mukomuko district is necessary to develop human resources which is an important factor for UKM players. Human Resource Development can be done with monitoring and traning. Insfrastructure development is an important factor for the empowerment of UMKM in production and marketing infrastructure with market development to support the growth of UMKM in Mukomuko District and monitoring of market management. Work programs are an important factor for the success of UMKM with the ability to develop business from the work programs made, business development is carried out with coaching during the Covid-19 Pandemic, UMKM experienced decreased income, decreased purchases, and were constrained in marketing and distribution of raw materials. late.Â Keywords: Institutional Manager of Micro, Small and Medium Business, Covid-19.